PEMBELAJARAN HUKUM PASCAL MENGGUNAKAN MINIATUR MESIN HIDROLIK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Heru Damayanti; Sutikno Sutikno; Masturi Masturi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This research is motivated from the results of the discussion with the teacher, the initial data in the form of a questionnaire completed and Physics teacher in classroom observations about the lack of utilization of instructional mediaand media appropriate learning materials specifically for Pascal law. Media were developed in the form of miniature forklift simple car specifically designed as an effective and efficient media which in addition can be as a demonstration tool can also be used to measure how much force ratio of each cross-section of the cross section. The method used is the method of Research and Development (R & D) by using a design model of the Borg & Gall. Steps study conducted by researchers to test phase products. Data retrieval instrument validation study media use a questionnaire to the media expert and material expert. Results of the research with the development of instructional media is expected to improve critical thinking skills, especially in the eighth grade physics lesson on materials Pascal Keywords: Instructional Media: Pascal Law; Critical Thingking.